Observation on Teachers’ Readiness for Implementation of Higher Order Thinking Skills (HOTS) in Technical and Vocational Education and Training (TVET) - Hashim, Suhaizal; Baharudin, Nurhayati; Abdul Rahman, Khairul Anuar; Hussin, Imran; Mohd Asri, Khairunisa; Zulkifli, Nurul Nadwa (Online Journal for TVET Practitioners, 2022)
Higher order Thinking Skills (HOTS) is an important element in achieving the nation’s objective of developing people with creative and analytical minds. However, there have been issues that impede teachers from implementing HOTS where certain teachers are not ready to implement HOTS knowledge to students, as well as insufficient training or HOTS related courses when they endure teaching training or have been employed as teachers. The purpose of this study was to determine the teachers’ level of readiness to face the changes in curriculum, pedagogy and assessment to implement HOTS in teaching. A validated questionnaire with an Alpha Cronbach's value of 0.874 was used as an instrument for this quantitative study. The research sample for this study consisted of 40 teachers with TVET background in Batu Pahat, Johor. The collected data were analyzed using the Statistical Package for Social Science version 21.0 in which the descriptive statistical method was used to determine the mean value and standard deviation. Based on the analysis, the results showed that the teachers had a high level of readiness to face the changes in curriculum aspect (mean=4.10, SD=0.39), the pedagogical aspect (M=4.00, SD=0.48) and the assessment aspect (M=4.08, SD=0.45). In addition, the relationships between curriculum, pedagogy and assessment of TVET teachers’ readiness on HOTS implementation were not statistically significant. In conclusion, it is hoped that this study could be used to serve as a guide for teachers to imply HOTS in their teaching and learning process in order to enhance students interested in TVET subject. Teachers therefore need to equip themselves with HOTS knowledge and skills so that they can facilitate learning, improve skills and increase student engagement in class.